THE EFFECTIVENESS OF INTERPERSONAL COMMUNICATION AS A GUIDANCE AND COUNSELING APPROACH IN THE SELECTION OF STUDY PROGRAMS AT MERCU BUANA UNIVERSITY FOR STUDENTS OF CLASS XII SMKN 60 JAKARTA - Salim, Muhammad Rizki; Tomohardjo, Irmulansati; Budianto, Heri (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
This study aims to evaluate the effectiveness of interpersonal communication as an approach in guidance and counseling for selecting study programs at Mercu Buana University for 12th-grade students at SMKN 60 Jakarta. Effective interpersonal communication between guidance counselors (BK) and students plays a crucial role in helping students understand their potential and interests, guiding them in making appropriate decisions regarding their choice of study programs in higher education. The research method used is qualitative with a case study approach, involving in-depth interviews, participatory observation, and document analysis. The results indicate that interpersonal communication conducted by BK teachers can enhance students' self-awareness, reduce anxiety in the decision-making process, and provide positive encouragement to achieve their academic goals. Furthermore, the supportive interactions and empathy shown by BK teachers significantly contribute to increasing students' confidence in choosing study programs that align with their interests and talents. This study concludes that the interpersonal communication approach in guidance and counseling is highly effective in assisting 12th-grade students at SMKN 60 Jakarta in selecting study programs at Mercu Buana University.